2014
DOI: 10.1016/j.cpc.2013.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Ray-tracing code TRAVIS for ECR heating, EC current drive and ECE diagnostic

Abstract: A description of the recently developed ray-tracing code TRAVIS is given together with the theoretical background, results of benchmarking and examples of application. The code is written for electron cyclotron studies with emphasis on heating, current drive and ECE diagnostic. The code works with an arbitrary 3D magnetic equilibrium being applicable for both stellarators and tokamaks. The equations for ray tracing are taken in the weakly relativistic approach, i.e. with thermal effects taken into account, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
109
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(113 citation statements)
references
References 62 publications
4
109
0
Order By: Relevance
“…For two magnetic equilibriums with the different "mirror-ratio", B max /B min = 1.36 and 1.64, two different scenarii were considered. Using the transport code [9] and ray-tracing code TRAVIS [5] coupled together, it was shown that by change of the launch direction by RSL or switching (on/off) of gyrotrons, the fraction of power absorbed from the X3 beam can be redirected from passing electrons to locally trapped ones. In experiments with rapid modulation of P trap abs /P total abs , additional convective (non-neoclassical) contributions to the radial transport can be expected.…”
Section: Iter and W7x Designmentioning
confidence: 99%
See 1 more Smart Citation
“…For two magnetic equilibriums with the different "mirror-ratio", B max /B min = 1.36 and 1.64, two different scenarii were considered. Using the transport code [9] and ray-tracing code TRAVIS [5] coupled together, it was shown that by change of the launch direction by RSL or switching (on/off) of gyrotrons, the fraction of power absorbed from the X3 beam can be redirected from passing electrons to locally trapped ones. In experiments with rapid modulation of P trap abs /P total abs , additional convective (non-neoclassical) contributions to the radial transport can be expected.…”
Section: Iter and W7x Designmentioning
confidence: 99%
“…Simulations have been performed with help of the generalized Spitzer function precalculated by the drift kinetic equation solver NEO-2 [4], which was applied as input for the ray-tracing code TRAVIS [5]. It was shown that in contrast to the asymptotic low and high collisionality limits, where the symmetric part of the Spitzer function is small, the direction of the current may become independent of the microwave beam launch angle in ECCD scenarii with relatively low single-pass absorption such as O2 and X3.…”
Section: Current Drive and Spitzer Problemmentioning
confidence: 99%
“…An additional equation can be added to provide the spatial evolution of the amplitude, as it is, for ray tracing code in toroidal geometry with adapted coordinate system, as it was done in Marushchenko et al 2014) or for Gaussian beam (Bertelli et al 2012). While the dispersion relation is known, it is possible to apply this tool if the initial conditions are also known.…”
Section: Heating Simulationmentioning
confidence: 99%
“…For this reason it is necessary to implement a feedback targeting system for the launcher mirrors. This will initially be implemented in a feed-forward scheme using the TRA-VIS code [6]. In addition a set RF probing holes have been added to the TZM tiles, which will be used to measure the shine-through power of the ECRH beam incident on the tile.…”
Section: Developments For Op12mentioning
confidence: 99%